High Speed Pneumatic Theory and Technology Volume I Servo System - Yin, Yaobao (Springer Nature Singapore : Imprint: Springer, 2019)
This book covers the author's research achievements and the latest advances in high-speed pneumatic control theory and applied technologies. It presents the basic theory and highlights pioneering technologies resulting from research and development efforts in aerospace, aviation and other major equipment, including: pneumatic servo control theory, pneumatic nonlinear mechanisms, aerothermodynamics, pneumatic servo mechanisms, and high-speed pneumatic control theory.